ROLE IN Obstetric Acupuncture - Harry Kurniawan Gondo (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
Term " acupuncture" coming from Latin Ianguage “acus” meaning needle, and punctura meaning to be jabed. InChinese, thousands of last year, noted that sore army effect of arrow sometime get over disease they which have suffer during through years. Emerge idea that, by jabing husk certain dot, disease will recover. Chineman start to imitate arrow effect, by jabing husk use needle. Acupuncture represent important shares in traditional medication Chinese, including other technique like "kop", "moxibustion", masase ("Tuina"), and Chinese herb drug. More than 20 the last year of popularitas acupuncture have mounted many shares in all the world. More and more interest to usage of acupuncture in practice midwifery. Organizational Health of World (WHO) express that there are complete evidence which supporting conducive acupuncture therapy effect become important shares in service of health of primary and that acupuncture have to fully integrated with conventional doctor.